Pengaruh Kualitas Audit Terhadap Hubungan Pengungkapan Other Comprehensif Income (OCI) dengan Earning Management - Rissi, Dita Maretha; Ermatati, Ermatati (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Change in accounting standards in Indonesia uses international standards became the focus of attention for company management because they had to report other comprehensive income (OCI). OCI components contain high assumptions, estimates and judgments from management, therefore high quality audits may reduce earnings management of OCI. The aim of this research is to analyze the effects of audit quality on relationship of other comprehensive income disclosure with earnings management. Research type is descriptive verification. The dependent variable in this research is the earnings management which proxy by discretionary accruals and use modified-Jones Model. Other comprehensive income as independent variable that measured by OCI ratio. While audit quality as moderator variable using dummy variable, KAP big four given a value of 1 and KAP non-big four given a value of 0. This research also use control variable and firm size as measured by total assets of the company and categorizing big and small companies by divided into 25% for the highest asset value for large companies and 25% of the lowest asset value for small companies. This research uses secondary data, financial data from the company’s official website and Icamel from 2019-2021. The sampling method used in this research is purposive sampling. Methods of data analysis in this research using multiple linear regression analysis, F-test and coefficient determination. The results of this research by F test with significant value 0.000 (<0.005) and the direction of negative coefficient indicates that there is significant influence of audit quality on the relationship of other comprehensive income disclosure with earnings management, a degree of influence is 18% as evidenced by the value of adjusted R2. Based on the results of the research are expected to related parties in the capital market may encourage capital market participants to optimize the information contained in the financial statements, including information on other comprehensive income.